Antusiasme Masyarakat dalam Program Mengajar dari Rumah (MDR) di Era Pandemi di Desa Penedagandor, Lombok Timur - Laily Fitriani Mulyani (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
One of the impacts of Covid-19 is in the field of education. The impact of Covid-19 is very felt by some people in rural areas who experience signal difficulties in their areas, high (expensive) internet quota, unequal internet quota assistance for parents of guardians, unfamiliar parents with internet, parents It is difficult to teach their children because many guardians of students in rural areas have dropped out of school, so the government has to make quick and accurate policies. One of the policies implemented by the Ministry of Education and Culture is to support the Teaching from Home Program (TFH). This activity involved 35 students who took part in the teaching and learning process and parents who gave permission for their child's participation. This study used a survey method and data collection using a questionnaire that has been distributed after the teaching and learning activities ended. The results of this questionnaire were analyzed using descriptive statistics using the SPSS computer program. Based on the results of the research that has been carried out, it is concluded that the activities of the Home Teaching Program have received positive responses and the community is very enthusiastic about this activity.